PARAMETER FOR SCALE-UP OF EXTRACTION CYMBOPOGON NARDUS DRY LEAF USING MICROWAVE ASSISTED HYDRO-DISTILLATION - MA`SUM, ZUHDI; MAHFUD, MAHFUD; ALTWAY, ALI (Journal of Applied Engineering Science, 2019)
Large capacity in extraction using the microwave hydrodistillation method is always a challenge to do. The biggest obstacle in this method is the limitations of microwaves penetrating the material. Besides that, the high heat produced due to molecular heating simultaneously causes some components to degrade and reduce the quality of essential oils. Research on the effect of load capacity on yields of Cymbopogon nardus using microwave equipment was carried out. This research compared the effect of different parameters time ekstraction and ratio feed to solvent (F/S). In the study also carried out a volume distiller comparison with microwave cavity volume (D/M). These research was performed microwave power irradiation at 100%, 80%, and 60% together feed to solvent ratio (F/S) 8%, 16% and 24% at ratio (D/M) of 0,04. Analysis of oil composition using GC MS was carried out to show that the length of extraction time did not provide an effect on changes in the composition of the oil extracted. The results of these experiments indicate that usage of 80% of microwave power irradiation and 16% ratio of feed to volume distiller together with 24% of feed to solvent ratio, effective to increase oil yields by up to 1,2. The same yield was obtained by increasing D/M ratio by increasing microwave power irradiation. Chemical composition of citronella oil was analyzed using GC MS. These citronella oil was found to contain mainly citronella, geraniol and citronellol, and with comprised percent area 40%, 17% and 16% respectively. Increasing microwave power irradiation does not significantly affect the final composition of extraction. The results show the possibility of increasing capacity using microwave-based extraction equipment. These results also have significant implications for the continuing use of microwaves in extraction applications and could be compromised to scale up capacity.